In the mouse, prostaglandin D2 signalling protects the endometrium against adenomyosis. (14th April 2021) - Philibert, Pascal; Déjardin, Stéphanie; Pirot, Nelly; Pruvost, Alain; Nguyen, Anvi Laetitia; Bernex, Florence; Poulat, Francis; Boizet-Bonhoure, Brigitte
Abstract: Adenomyosis is characterised by epithelial gland and mesenchymal stroma invasion of the uterine myometrium. Adenomyosis is an oestrogen-dependent gynaecological disease in which a number of factors, such as inflammatory molecules, prostaglandins (PGs), angiogenic factors, cell proliferation and extracellular matrix remodelling proteins, also play a role as key disease mediators. In this study, we used mice lacking both lipocalin and hematopoietic- PG D synthase (L- and H -Pgds ) genes in which PGD2 is not produced to elucidate PGD2 roles in the uterus. Gene expression studied by real-time PCR and hormone dosages performed by ELISA or liquid chromatography tandem mass spectroscopy in mouse uterus samples showed that components of the PGD2 signalling pathway, both PGDS and PGD2-receptors, are expressed in the mouse endometrium throughout the oestrus cycle with some differences among uterine compartments. We showed that PGE2 production and the steroidogenic pathway are dysregulated in the absence of PGD2. Histological analysis of L/H-Pgds −/− uteri, and immunohistochemistry and immunofluorescence analyses of proliferation (Ki67), endothelial cell (CD31), epithelial cell (pan-cytokeratin), myofibroblast (α-SMA) and mesenchymal cell (vimentin) markers, identify that 6-month-old L/H-Pgds −/− animals developed adenomyotic lesions, and that disease severity increased with age. In conclusion, this study suggests that the PGD2 pathway has major roles in the uterus by protecting the endometrium against adenomyosis development. Additional experiments, using for instance transcriptomic approaches, are necessary to fully determine the molecular mechanisms that lead to adenomyosis in L/H-Pgds −/− mice and to confirm whether this strain is an appropriate model for studying the human disease.